CACCI country profile Papua New Guinea - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Papua New Guinea ranks among the countries most at risk to natural disasters and climate change (World Bank, 2021). Increased exposure to natural hazards such as coastal and inland river flooding as well as landslides are likely to intensify in PNG, affecting agriculture production patterns and household livelihoods. In addition, the IPCC’s 5th Assessment Report suggests that Pacific coral reefs face a negative outlook under all climate change scenarios, whereby increased coral bleaching will have significant negative impacts on the health of coastal fisheries in PNG (Nurse et al., 2014).